Tripeptide Interference with Human Immunodeficiency Virus Type 1 Morphogenesis - Höglund, Stefan (American Society for Microbiology, 2002)
Capsid assembly during virus replication is a potential target for antiviral therapy. The Gag polyprotein is the main structural component of retroviral particles, and in human immunodeficiency virus type 1 (HIV-1), it contains the sequences for the matrix, capsid, nucleocapsid, and several small polypeptides. Here, we report that at a concentration of 100 μM, 7 of 83 tripeptide amides from the carboxyl-terminal sequence of the HIV-1 capsid protein p24 suppressed HIV-1 replication (>80%). The three most potent tripeptides, glycyl-prolyl-glycine-amide (GPG-NH(2)), alanyl-leucyl-glycine-amide (ALG-NH(2)), and arginyl-glutaminyl-glycine-amide (RQG-NH(2)), were found to interact with p24. With electron microscopy, disarranged core structures of HIV-1 progeny were extensively observed when the cells were treated with GPG-NH(2) and ALG-NH(2). Furthermore, nodular structures of approximately the same size as the broad end of HIV-1 conical capsids were observed at the plasma membranes of treated cells only, possibly indicating an arrest of the budding process. Corresponding tripeptides with nonamidated carboxyl termini were not biologically active and did not interact with p24.